Parenting and healthy teenage lifestyles. The balance of the AS - Paloma Alonso Stuyck (INFAD, 2020)
The current emergency of promoting healthy lifestyles is well known. These lifestyles are shaped and driven by sociocultural and individual behavior patterns. Parenting styles carry great weight in regard to this endeavor, especially in adolescence, a time in which autonomous decision-making starts. Thescope ofadolescent decision-making is gained as parentscede their own authority with this process becoming a balance between parental Authority and teenage child Autonomy: balancing the As. In this process, discrepancy as to who is responsible for deciding is frequent between parent and teenage child. Parenting styles which are able to adjust expectations between parents and adolescents by focusing on the teachable dimensions of the person are proposed. These parenting styles create the right environment to establish affective dialoguesin regard to specific behaviorsand generateassertive disciplinechannels. The main advantage of these parenting styles rooted in the cognitive, conative and affective dimensions of children is that they can be adapted to different socio-cultural contexts. By promoting adolescent autonomy they promote the internalization of long-term healthy lifestyles. Adolescence is presented as a sensitive period in which to adopt healthy lifestyles.